2018
DOI: 10.1016/j.cell.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Flavivirus-Host Protein Interaction Mapping Reveals Mechanisms of Dengue and Zika Virus Pathogenesis

Abstract: Mosquito-borne flaviviruses, including dengue virus (DENV) and Zika virus (ZIKV), are a growing public health concern. Systems level analysis of how flaviviruses hijack cellular processes through virus-host protein-protein interactions (PPIs) provide information about their replication and pathogenic mechanisms. We used affinity purification-mass spectrometry (AP-MS) to compare flavivirus-host interactions for two viruses (DENV and ZIKV) in two hosts (human and mosquito). Conserved virus-host PPIs revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
355
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 272 publications
(399 citation statements)
references
References 81 publications
29
355
0
2
Order By: Relevance
“…To test whether pharmacological inhibition of the Sec61 translocon complex phenocopies the genetic knockdown, we treated cells with SEC61 inhibitors, CT8 (22) and PS3061 (24). We observed that treatment of MM cell lines with increasing concentrations of these compounds results in an up to five-fold dose-dependent increase in cell-surface BCMA levels and a decrease in cell surface CD38 levels, as evidenced by flow cytometry (Figs.…”
Section: The Sec61 Translocon Regulates Bcma Protein Levelsmentioning
confidence: 97%
“…To test whether pharmacological inhibition of the Sec61 translocon complex phenocopies the genetic knockdown, we treated cells with SEC61 inhibitors, CT8 (22) and PS3061 (24). We observed that treatment of MM cell lines with increasing concentrations of these compounds results in an up to five-fold dose-dependent increase in cell-surface BCMA levels and a decrease in cell surface CD38 levels, as evidenced by flow cytometry (Figs.…”
Section: The Sec61 Translocon Regulates Bcma Protein Levelsmentioning
confidence: 97%
“…3). We studied the interacting human proteins in regards to their cell biology, anatomical expression patterns, expression changes during SARS-CoV-2 infection 21 and in relation to other maps of pathogen interacting proteins 19,[22][23][24][25][26][27][28][29][30] (Fig. 2a).…”
Section: Global Analysis Of Sars-cov-2 Host Interacting Proteinsmentioning
confidence: 99%
“…In addition to its role in STAT2 degradation, DENV NS5 protein is also able to interfere with ISG expression. First, both DENV and ZIKV NS5 selectively inhibit ISG expression by binding to and antagonizing the transcription factor PAF1C [125]. Second, DENV NS5 hijacks core components of the spliceosomal machinery, namely CD2BP2 and DDX23, resulting in an alteration of isoform abundance and stoichiometry of many antiviral factors such as RIG-I, ISG15, or IL-8, hence contributing to an environment favourable to viral replication [126].…”
Section: Interference With Other Mechanismsmentioning
confidence: 99%
“…This shows that sfRNA plays two distinct roles, albeit using the same cellular factors, in the evasion of the innate immune response in mammalian hosts or arthropod vectors. This concept of different roles of host factors between the mammalian hosts or arthropod vectors will most likely be explored in depth in the future considering that a recent system biology study identified more than 45 shared pathway interactions between DENV-human and DENV-mosquito interactomes in the context of innate immune evasion and viral pathogenesis [125].…”
Section: Interference With Other Mechanismsmentioning
confidence: 99%